The Effect of Blended Learning on Student Learning Outcomes in Software Application Subjects and Building Interior Design at SMK Negeri 2 Surabaya - Firmansyah, Aditya Arie; Dwi Mulyono, Wahyu (Universitas Nahdatul Ulama Surabaya, 2022)
Covid-19 is a virus that has caused a pandemic throughout the world including Indonesia since 2020. This has hampered all aspects of life, one of which is the education aspect. By the end of 2020, many schools in Indonesia were implementing mixed learning-based learning between online, offline, and independent learning, or what could be called blended learning. To see whether or not there is an effect of blended learning-based learning on student learning outcomes in the subjects of Software Applications and Building Interior Design, this research was conducted. Class XI DPIB SMK Negeri 2 Surabaya students were the sample in this study. Ex post facto is the method used by researchers in compiling this research. Ex post facto is research that looks for a causal relationship without any special treatment. In this study, a questionnaire was used as a research instrument containing 17 statements with 36 students as respondents. The time of research was carried out in the 2021/2022 academic year. The analysis carried out resulted in a conclusion, namely (1) The results of the questionnaire analysis on the implementation of blended learning at SMK Negeri 2 Surabaya got an average of 3.21 with a sufficient/normal category. (2) There is an increase in student learning outcomes from semester 1 to semester 2. (3) There is an effect that occurs on the X variable on the Y variable, the effect of blended learning on learning outcomes is positive. The magnitude of the effect of blended learning on student learning outcomes is 21.7%. then the other 78.9% are variables that are not studied.